Polyethyleneimine‐Polyoxometalate‐Based Supramolecular Self‐assembled pH‐Responsive Hydrogels: Formulation and in vitro Evaluation. Issue 21 (25th July 2017) - Azizullah,; Haider, Ali; Kortz, Ulrich; Joshi, Sachin A.; Iqbal, Jamshed
Abstract: In the present study electrostatically‐driven pH responsive supramolecular, self‐assembled hydrogels of the trilacunary Wells‐Dawson‐type 15‐tungsto‐2‐phosphate polyanion [P2 W15 O56 ] 12− (P2 W15 ) and polyethyleneimine were prepared. Crosslinking was achieved through electrostatic interactions between cationic polyethyleneimine andP2 W15 . The pH responsiveness was induced by acrylic acid. Benzoyl peroxide was used as an initiator, for initiating the polymerization reaction, anchoring polyacrylic acid on the polyethyleneimine skeleton. The prepared sea‐green color hydrogels were characterized by FT‐IR, SEM, XRD and thermal analysis (TGA‐DSC). The swelling index, P2 W15 release studies and pH responsive properties of the developed supramolecular hydrogels were evaluated at pH 1.2 and 7.4, showing maximum swellability and release characteristics at pH 7.4. For determining theP2 W15 release mechanism different mathematical models such as zero order, first order, Higuchi model and Krosmeyer‐Peppas models were applied and the results showed that embeddedP2 W15 release follows zero‐order kinetics. The cytotoxicity results showed that naked and embeddedP2 W15 exhibited dose‐dependent cytotoxicity against cancer cell lines (MCF‐7; Hela) with minimal effects on normal cells (Vero). The hydrogels developed through electrostatic interactions exhibited desirable qualities of a drug delivery system that can be used for the delivery of the embedded polyanion. Abstract : Supramolecular self‐assembled pH responsive hydrogels of polyethyleneimine and Wells‐Dawson type heteropolytungstate P2 W15 were prepared through electrostatic interactions characterized through different analytical techniques confirming the successful hydrogel formation. Maximum swelling and polyanion release was observed at pH 7.4, with minimum swelling and polyanion release at pH 1.2. Both free polyanion as well as embedded polyanion exhibited a dose dependent anticancer potential against both MCF‐7 and HeLa cells, whereas the polyanion was more efficient against normal Vero cells than doxorubicin.